Effects of the Great Recession on suicide mortality in Chile and contributing factors - Fernando Baeza; Francisca González; Tarik Benmarhnia; Alejandra Vives Vergara (Elsevier, 2022)
Between 2008 and 2009 suicide rates in Chile were higher than those observed before and after, increasing more than in other countries in Latin America. The Great Recession has been suggested as an important factor behind this increase. This study assesses the excess of suicide attributable to the crisis in Chile, a "mature" neoliberal society with a precarious social security system, low salaries, and high levels of indebtedness, and identifies the most relevant economic variables that may contribute to this excess. We pooled data since 2000 on monthly suicide rates, unemployment, economic activity and perception of problematic indebtedness for different sex and age groups. We adopted an interrupted time series design with Poisson regressions models adjusted for monthly variations and non-linear pre-crisis trajectories via restricted cubic splines. We then further controlled for economic variables to evaluate their possible contributions to suicide increase attributable to the economic crisis. Suicide mortality during the crisis period was higher than in the previous period in all sex and age groups. Overall, we estimated that 301 suicides (95% CI: 181 to 422) were attributable to the crisis in Chile. This excess was concentrated among men younger than 65 and women 65 and older. Including unemployment and indebtedness perception in the models reduced the excess of suicides. The increase was concentrated in the first half of the crisis and an early pre-crisis effect could be observed when anticipating the crisis beginning by three months. Results suggest that the Great Recession had an impact on suicide mortality in Chile and that increase in unemployment and indebtedness could be related to this increase. Results by sex and age are consistent with the most vulnerable groups in the context of Chilean neoliberalism. For future crises, improving unemployment insurance, and reinforcing suicide prevention attending to the economic context should be a priority.